Game audio development with Unity 5.X : design a blockbuster game soundtrack with Unity 5.X - Lanham, Micheal (Packt Publishing, 2017)
Create AAA' quality game audio with new features and tools built for UnityAbout This Book* Explore the basics of audio development in Unity to create spatial sound, mixing, effects, composition, adaptive audio and more.* Leverage the Audio Mixer of Unity 5.x to create blockbuster sound and music for your game.* Learn about developing professional audio for games with FMOD Studio and composing original music with Reaper.* Build amazing audio synchronized graphic visualizations with Unity.* Understand how real-time character lip syncing can be implemented. Who This Book Is ForThe ideal target audience for this book will be game developers, both Indie as well as semi pro. No prior knowledge of Unity and audio development is assumed, What You Will Learn* Develop game audio and other audio effects with Unity* Getting familiar with the new Audio Mixer introduced in Unity 5* Implement dynamic and adaptive audio using various tools and strategies* Explore interesting ways to incorporate audio into a game with sound visualization* Use 3rd party professional audio development tools like FMOD* Compose original music and record vocals* Understand and troubleshoot audio performance issuesIn DetailGame Audio is one of the key components in making a game successful and it is quite popular in the gaming industry. So if you are a game developer with an eye on capturing the gamer market then this book is the right solution for you. In this book, we will take you through a step by step journey which will teach you to implement original and engaging soundtracks and SFX with Unity 5.x. You will be firstly introduced to the basics of game audio and sound development in Unity. After going through the core topics of audio development: audio sources, spatial sound, mixing, effects, and more; you will then have the option of delving deeper into more advanced topics like dynamic and adaptive audio. You will also learn to develop dynamic and adaptive audio using the Unity Audio Mixer. Further, you will learn how professional third party tools like FMOD are used for audio development in Unity. You will then go through the creation of sound visualization techniques and creating your own original music using the simple yet powerful audio workstation Reaper. Lastly, you will go through tips, techniques and strategies to help you optimize game audio performance or troubleshoot issues. At the end of the book, you'll have gained the skills to implement professional sound and music. Along with a good base knowledge audio and music principles you can apply across a range of other game development tools. Style and approachThis book will have a step by step practical approach where downloadable free games will be given with the book and readers will be free to work with them.